A 20-year vegetation cover change and its response to climate factors in the Guangdong-Hong Kong-Macao Greater Bay Area under the background of climate change - Feng, Xianhui; Zeng, Zhilin; He, Mu (Frontiers in Ecology and Evolution, 2023)
The Guangdong-Hong Kong-Macao Greater Bay Area (GBA) has located in the south subtropical area along the southeast coast of China, which is one of the world-class urban agglomerations and an important part for economic development. In order to investigate the change of vegetation indexes and its response to climate factors in such circumstance of climate change, this study is an important component in the protection and establishment of the ecological environment in the GBA. The Moderate Resolution Imaging Spectroradiometer-Enhanced Vegetation Index (MODIS-EVI) and climate data were recorded from National Aeronautics and Space Administration (NASA) and Resource and Environment Science Data Center of the Chinese Academy of Sciences. Trend analysis, Mann-Kendall (MK) Test and rescaled range analysis (R/S Analysis) offer an effective way of analyzing the correlation between the vegetation cover change and climate factors. The results provide important insights into following aspects: (1) the changes of climate factors (temperature, precipitation, wind speed, humidity and sunshine radiation) are fluctuated in GBA, with no obvious increasing or decreasing trend. It comprehensively exhibited an extremely slow development of humidify and warming. (2) it presents an increasing trend of EVI in GBA, with the rate of 0.0045/a. the range of increase is in the middle level (0.4≤EVI＜0.6) based on the EVI. The vegetation cover in GBA is improved comprehensively, the area of vegetation improvement is larger than the area of vegetation degression, with the extremely improved vegetation cover area (66.98%) and the extremely degraded vegetation cover area (5.70%). There are obvious differences and agglomerations in the distribution of the EVI trends. (3) In future, the changing trends will be combinedly affected be various factors, and there is no obvious factor temporarily. The improved vegetation cover area (over 80%) are predicted. (4) There are significant spatiotemporal differences in the annual effects of EVI on various climate factors comprehensively. Wind speed and relative humidity have the strongest correlations with EVI; the area of significant correlation is more than 40% of the pixels. The correlation between temperature and EVI is second, with the area of significant correlation over 20% of the pixels.